«Los ángeles no se discuten»: la legitimación de la figura de María de las Mercedes de Orleans - Berta Lillo-Gutiérrez (Cahiers de Civilisation Espagnole Contemporaine)
This article analyses the legitimizing construction that surrounded Queen María de las Mercedes de Orleans, first wife of Alfonso XII. The brevity of her reign, which lasted less than half a year, has meant that her public image has not been studied in detail despite the interesting discourse surrounding her. Her figure, and therefore her legitimacy as queen, remained shrouded after her death in a romantic halo, but upon close examination, ignoring the influence of later mythification, other key legitimising elements emerge. At a time of consolidation of liberalism in which the monarchy had to adapt in order to survive, the religion, qualities or nationality of the royal consorts became important, for as representatives of the nation they had to embody it and serve as a model. Therefore, the monarchy had to build a solid image that would popularize the queens and, by extension, solidify its role in the national conception.